Strengthening Character Education Through Scouts and Rebano Extracurricular Activities - Lidiah, Lidiah; Houtman, Houtman; Fatawi, Izzul (Journal of Social Work and Science Education, 2025)
This study aims to describe the planning, implementation, monitoring, and evaluation processes, as well as the supporting and inhibiting factors in strengthening character education through the Scout and Rebana extracurricular activities at SDN 1 Banyuasin III. The study employed a qualitative approach with a case study method. Data were obtained through in-depth interviews, participant observation, and document analysis, which were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that character education strengthening has been systematically integrated into both extracurricular activities. In the Scout activities, the characters of discipline, responsibility, and cooperation are the primary focus, while in Rebana, the values of religiosity, tolerance, and solidarity are emphasized. Activity planning is carried out through coordination meetings with the instructor and school officials, activities are implemented according to a pre-agreed routine schedule, and supervision is carried out directly by the instructor. Evaluations are conducted periodically to assess the achievement of character goals. Supporting factors include full support from the principal, the availability of competent instructors, and student enthusiasm. Inhibiting factors include limited infrastructure and scheduling conflicts with other activities. This study concludes that the extracurricular activities of Scouting and Rebana play a strategic role in shaping student character aligned with the Pancasila Student Profile. The implications of this research are the need to optimize facilities, increase the capacity of instructors, and foster synergy between schools, parents, and the community to strengthen the implementation of character education in elementary schools.